Small beetle, large‐scale drivers: how regional and landscape factors affect outbreaks of the European spruce bark beetle. Issue 2 (14th October 2015) - Seidl, Rupert; Müller, Jörg; Hothorn, Torsten; Bässler, Claus; Heurich, Marco; Kautz, Markus
Summary: Unprecedented bark beetle outbreaks have been observed for a variety of forest ecosystems recently, and damage is expected to further intensify as a consequence of climate change. In Central Europe, the response of ecosystem management to increasing infestation risk has hitherto focused largely on the stand level, while the contingency of outbreak dynamics on large‐scale drivers remains poorly understood. To investigate how factors beyond the local scale contribute to the infestation risk from Ips typographus (Col., Scol.), we analysed drivers across seven orders of magnitude in scale (from 10 3 to 10 10 m²) over a 23‐year period, focusing on the Bavarian Forest National Park. Time‐discrete hazard modelling was used to account for local factors and temporal dependencies. Subsequently, beta regression was applied to determine the influence of regional and landscape factors, the latter characterized by means of graph theory. We found that in addition to stand variables, large‐scale drivers also strongly influenced bark beetle infestation risk. Outbreak waves were closely related to landscape‐scale connectedness of both host and beetle populations as well as to regional bark beetle infestation levels. Furthermore, regional summer drought was identified as an important trigger for infestation pulses. Large‐scale synchrony and connectivity are thus key drivers of the recently observed bark beetle outbreak in the area. Synthesis and application s. Our multiscale analysis provides evidence that the risk for biotic disturbances is highly dependent on drivers beyond the control of traditional stand‐scale management. This finding highlights the importance of fostering the ability to cope with and recover from disturbance. It furthermore suggests that a stronger consideration of landscape and regional processes is needed to address changing disturbance regimes in ecosystem management. Abstract : Our multiscale analysis provides evidence that the risk for biotic disturbances is highly dependent on drivers beyond the control of traditional stand‐scale management. This finding highlights the importance of fostering the ability to cope with and recover from disturbance. It furthermore suggests that a stronger consideration of landscape and regional processes is needed to address changing disturbance regimes in ecosystem management.